Implant Alignment and Patient Factors Affecting the Short-Term Patient-Reported Clinical Outcomes after Oxford Unicompartmental Knee Arthroplasty - Yamagami, Ryota; Inui, HIroshi; Taketomi, Shuji; Kono, Kenichi; Kawaguchi, Kohei; Takagi, Kentaro; Kage, Tomofumi; Sameshima, Shin; Tanaka, Sakae (The Journal of Knee Surgery, 2020)
This study aims at clarifying implant alignment and other patient factors' influence on clinical outcomes, particularly on patient-reported outcomes (PRO), following Oxford unicompartmental knee arthroplasty (OUKA). A total of 142 patients after OUKA were divided into two groups according to the validated Japanese version of the knee injury and osteoarthritis outcome score (KOOS) for each subscale of pain, symptoms, and activities of daily living (ADL) at postoperative year 1 and 2: group 1 had ≥80 scores and group 2 had <80 scores. Postoperative clinical and radiographical findings were then compared among groups in each subscale. Using postoperative year 1 and 2 data, a multivariable logistic regression analysis was conducted to clarify factors for clinical outcomes' improvement. In the analysis of KOOS subscale of symptoms at postoperative year 1, gender distribution, preoperative body mass index, and postoperative maximum knee flexion angles differed significantly among groups. In the analysis for KOOS subscale of ADL, significant differences were observed in postoperative tibial component varus angles. Multivariable logistic regression analysis revealed that all of these parameters significantly related to ≥80 KOOS scores of each subscale at postoperative year 1. Additionally, at postoperative year 2, larger postoperative knee flexion angles and tibial component varus angles related to ≥80 KOOS subscale of symptoms and ADL were observed. In conclusion, tibial component's larger varus alignment was associated with the better PRO at both 1 and 2 years after OUKA. Importantly, larger postoperative knee flexion angle helped achieve good short-term PRO after OUKA.
Keywords: unicompartmental knee arthroplasty; patient-reported outcome; implant alignment; limb alignment; knee injury and osteoarthritis outcome score